Effects of Rising Temperature on the Growth, Stoichiometry, and Palatability of Aquatic Plants - Zhang, Peiyu; Grutters, Bart M. C.; van Leeuwen, Casper H. A.; Xu, Jun; Petruzzella, Antonella; van den Berg, Reinier F.; Bakker, Elisabeth S. (Frontiers in Plant Science, 2019)
Global warming is expected to strengthen herbivore-plant interactions leading to enhanced top-down control of plants. However, latitudinal gradients in plant quality as food for herbivores suggest lower palatability at higher temperatures, but the underlying mechanisms are still unclear. If plant palatability would decline with temperature rise, then this may question the expectation that warming leads to enhanced top-down control. Therefore, experiments that directly test plant palatability and the traits underlying palatability along a temperature gradient are needed. Here we experimentally tested the impact of temperature on aquatic plant growth, plant chemical traits (including stoichiometry) and plant palatability. We cultured three aquatic plant species at three temperatures (15, 20 and 25ºC), measured growth parameters, determined chemical traits and performed feeding trial assays using the generalist consumer Lymnaea stagnalis (pond snail). We found that rising temperature significantly increased the growth of all three aquatic plants. Plant nitrogen (N) and phosphorus (P) content significantly decreased, and carbon (C) :N and C:P stoichiometry increased as temperature increased, for both Potamogeton lucens and Vallisneria spiralis, but not for Elodea nuttallii. By performing the palatability test, we found that rising temperatures significantly decreased plant palatability in P. lucens, which could be explained by changes in the underlying chemical plant traits. In contrast, the palatability of E. nuttallii and V. spiralis was not affected by temperature. Overall, P. lucens and V. spiralis were always more palatable than E. nuttallii. We conclude that warming generally stimulates aquatic plant growth, whereas the effects on chemical plant traits and plant palatability are species-specific. These results suggest that the outcome of the impact of temperature rise on macrophyte stoichiometry and palatability from single-species studies may not be broadly applicable. In contrast, the plant species tested consistently differed in palatability, regardless of temperature, suggesting that palatability may be more strongly linked to species identity than to intraspecific variation in plant stoichiometry.